STEPPING THROUGH EDUCATION: EDUCATION TRANSFORMATION OF CHILDREN OF IMMIGRANT WORKERS (ILLEGAL) KOTA KINABALU WITH THE SUPPORT OF SIKK IN COLLABORATION WITH UIN SALATIGA - Afuza Luqyanata Awwaly Al emza; Dias Ayu Miftakhul Jannah; Resyta Laras Pradani; Tantri Hayuningtyas; Rilia Dian Pramesti (ALKADIMAT, 2023)
This research employs a qualitative research method, specifically a ( Case Study ) to depict the life transformation of children of illegal immigrant workers in Kota Kinabalu through educational access. The primary focus is on the support provided by SIKK and UIN Salatiga. Through the case study approach, the research delves deep into the specific context, dynamics of relationships, and the comprehensive impact of education on the lives of these children. The findings offer profound insights into how education can be a key to overcoming their life challenges, highlighting the positive potential of cross-institutional collaboration between SIKK and UIN Salatiga in supporting this transformative process.The education of children of Indonesian Migrant Workers is an important issue in Sabah,therefore it is an important effort of UIN Salatiga in handling education Children of Indonesian Migrant Workers in Sabah. Efforts made between UIN Salatiga which will cooperate with SIKK. Result between the two parties, Sekolah Kota Kinabalu (SIKK) and UIN Salatiga held scholarships for children attending SIKK.